Synergy between Digitalization and Performance of Moroccan Public Universities: The Mediating Role of Technological Innovation - Housni, Said; Fekkak, Azzeddine; Imass, Lahcen; Akdim, Ahmed (International Review of Management and Marketing, 2026)
In Morocco, digitalization has become a strategic priority in socio-economic development policies, with public authorities implementing structural strategies to support digital transformation in public institutions. Beyond the mere dematerialization of processes, digitalization challenges traditional organizational models and compels public institutions to rethink governance and operational practices. By adopting a quantitative approach, this study investigates the role of technological innovation in mediating the relationships between digitalization and the performance of public services in Moroccan public universities. Using the Partial Least Squares Structural Equation Modelling (PLS-SEM), the findings reveal that the adoption of digitalization has a low direct effect on university performance (β = 0.043, P ⩽ 0.050). Moreover, technological innovation exerts a significant mediating effect (β = 0.16, p = 0.021), affirming its central role in improving the impact of digitalization on the performance of Moroccan public universities.